Direct CFD simulations of standard maneuvering tests for DARPA Suboff. (15th May 2023) - Delen, Cihad; Kinaci, Omer Kemal
Abstract: Maneuvering abilities of underwater vehicles are one of the primary concerns for navies and in the civil field they provide great flexibility in working in confined environments. Numerical simulations of the motions of these vessels may be conducted via system-based or direct CFD approaches. In this study, we focus on direct CFD simulations of the benchmark DARPA Suboff AFF8 Configuration. The paper starts by showing the submarine's lack of course-keeping stability using the C-index. After validation of the numerical approach by self-propulsion tests (and the determination of the propeller rotation rate to achieve the required velocity), the results of an extensive set of standard maneuvering tests are presented. Turning circle, pullout and zig-zag tests confirm that the DARPA Suboff does not have course-keeping ability. The submarine leans to the starboard side at neutral rudder angle. The maneuvering indices are investigated with respect to changing rudder angle with turning circle tests. High residual yaw rates are found in both side turnings in the pullout tests and the zig-zag tests show the submarine's inadequacy in making sharp turns. Numerical simulations reveal that the DARPA Suboff has high turning ability but no course-keeping ability. Highlights: Maneuvering performance of a submerged hull (DARPA Suboff) was determined using standard maneuvering tests. The effect of rudder angle (−35.0 ≤ δ ≤ 35.0) on the turning circle maneuver was investigated by direct CFD simulations. Pullout tests revealed an excessive residual yaw rate indicating the lack of course-keeping stability. The lack of course-keeping stability was also effective in zigzag maneuver as the ship barely managed to complete the tests.